THE BANKS GUARANTEE UNDER THE UNIFORM INTERNATIONAL RULES - Chipashvili, Nino (European Scientific Journal, ESJ, 2014)
The UN Commission on International Trade Law (UNCITRAL) officially endorsed the most recent revision of the ICC Uniform Rules for Demand Guarantees (URDG N 758) at its 44th annual session in Vienna from 27 June-8 July 2011. It became effective on July 1, 2010. Jean-Guy Carrier, ICC Secretary-General said: The UNCITRAL endorsement of the ICC URDG will undoubtedly define the direction of banking practice for demand guarantees, establish international unity with regards to these practices, and alleviate any confusion and miscommunication which could arise in the completion of trade transactions” [10]. Clear, precise and comprehensive new rules aim to maintain legal risk control through the high level of certainty and predictability that they foster. The interest of financial stability of business entities and the desire to quickly collect receivables need a legal instrument for security payments which provide safety to business partners to the fullest extent and will minimize the effect of risk factors. From the number of these instruments, the bank guarantee is the most important security instrument for contemporary circulation of commodities in the world. In this work, the object and purpose of the study is to analyze the legal aspects and results when using the international banking guarantees and are based on the theoretical methodology of scientific research.